The origin of photoluminescence in amorphous lead titanate - Leite, E. R.; Paris, E. C.; Pontes, F. M.; Paskocimas, C. A.; Longo, Elson [UNESP]; Sensato, F.; Pinheiro, C. D.; Varela, José Arana [UNESP]; Pizani, P. S.; Campos, CEM; Lanciotti, F. (Kluwer Academic Publ, 2003)
We discuss the nature of visible photoluminescence at room temperature in amorphous lead titanate in the light of the results of recent experimental and theoretical calculations. Experimental results obtained by XANES and EXAFS revealed that amorphous lead titanate is composed of a Ti-O network having fivefold Ti coordination and NBO-type (non-bridging oxygen) defects. These defects can modify the electronic structure of amorphous compounds. Our calculation of the electronic structure involved the use of first-principle molecular calculations to simulate the variation of the electronic structure in the lead titanate crystalline phase, which is known to have a direct band gap, and we also made an in-depth examination of amorphous lead titanate. The results of our theoretical calculations of amorphous lead titanate indicate that the formation of fivefold coordination in the amorphous system may introduce delocalized electronic levels in the HOMO ( highest occupied molecular orbital) and the LUMO ( lowest unoccupied molecular orbital). A comparison of the experimental and theoretical results of amorphous compounds suggests the possibility of a radiative recombination (electron-hole pairs), which may be responsible for the emission of photoluminescence. (C) 2003 Kluwer Academic Publishers.